2014
DOI: 10.3899/jrheum.140167
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Arthritis Referral Study — Phase 2: Analysis of the Comprehensive Arthritis Referral Tool

Abstract: A 1-page referral tool that includes parts completed by the referring physician and patient has good sensitivity to detect urgent referrals including EIA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
20
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 29 publications
2
20
1
Order By: Relevance
“…Indeed, a study of rheumatology clinic referrals found self-reported family history of RA associated with lower chance of having inflammatory arthritis 27. Our data, however, do not indicate any such strong effect in Sweden.…”
Section: Discussioncontrasting
confidence: 80%
“…Indeed, a study of rheumatology clinic referrals found self-reported family history of RA associated with lower chance of having inflammatory arthritis 27. Our data, however, do not indicate any such strong effect in Sweden.…”
Section: Discussioncontrasting
confidence: 80%
“…Unlike many other triage systems [17,18], CReATe Rheum does not require involvement of a rheumatologist in the initial triage of most patients, which is very important due to the shortage of specialists. Evidence supports the integration of alternate care providers in the care of patients with rheumatic diseases as it frees the specialist physician's time for care of more complex patients [19,20].…”
Section: Page 13mentioning
confidence: 99%
“…22 The tool appears to work well in this respect, with a sensitivity of 90.5% for the detection of urgent referrals. However, as with the PRS, it does not deal with the more difficult question of prioritizing access.…”
Section: Discussionmentioning
confidence: 97%
“…20 This information was absent from 64.9% Acute monoarthritis with specific concern for septic arthritis Giant cell arteritis-significant concern for a diagnosis of giant cell arteritis Acute systemic vasculitis-significant concern for acute development of a systematic vasculitis with major organ involvement, eg, acute pulmonary, cardiac, renal, gastrointestinal, or neurological features; cutaneous vasculitis or digital infarcts Acute connective tissue disease-significant concern for acute development of a connective tissue disease with major organ involvement, eg, acute pulmonary, cardiac, renal, hematological, neurological features; cutaneous vasculitis or digital infarcts Significant unexplained constitutional symptoms of either fever >38°C or weight loss >5% in preceding 6 wk, where there is a strong suspicion that it may relate to a connective tissue disease of referrals in a review of referrals to rheumatology services in the United Kingdom. 21 We acknowledge that people stop work for a wide variety of reasons, and whereas this may not be an important distinguishing factor in the determination of early inflammatory arthritis, 22 it is an important domain to gauge the effect of the problem on the individual. The associated definition makes clear that this domain should be scored with reference to the current condition and not preexisting or other factors.…”
Section: Discussionmentioning
confidence: 99%